Mycobacterium canettii Infection of Adipose Tissues - Bouzid, Fériel; Brégeon, Fabienne; Poncin, Isabelle; Weber, Pascal; Drancourt, Michel; Canaan, Stéphane (Frontiers in Cellular and Infection Microbiology, 2017)
Adipose tissues were shown to host Mycobacterium tuberculosis which is persisting inside mature adipocytes. It remains unknown whether this holds true for Mycobacterium canettii, a rare representative of the M. tuberculosis complex responsible for lymphatic and pulmonary tuberculosis. Here, we infected primary murine white and brown pre-adipocytes and murine 3T3-L1 pre-adipocytes and mature adipocytes with M. canettii and M. tuberculosis as a positive control. Both mycobacteria were able to infect 18-22% of challenged primary murine pre-adipocytes; and to replicate within these cells during a 7-day experiment with the intracellular inoculums being significantly higher in brown than in white pre-adipocytes for M. canettii (p = 0.02) and M. tuberculosis (p = 0.03). Further in-vitro infection of 3T3-L1 mature adipocytes yielded 9% of infected cells by M. canettii and 17% of infected cells by M. tuberculosis (p = 0.001). Interestingly, M. canettii replicated and accumulated intra-cytosolic lipid inclusions within mature adipocytes over a 12-day experiment; while M. tuberculosis stopped replicating at day 3 post-infection. These results indicate that brown pre-adipocytes could be one of the potential targets for M. tuberculosis complex mycobacteria; and illustrate differential outcome of M. tuberculosis complex mycobacteria into adipose tissues. While white adipose tissue is an unlikely sanctuary for M. canettii, it is still an open question whether M. canettii and M. tuberculosis could persist in brown adipose tissues.